Physical activity and cancer survival: the role of peripheral blood immune and inflammatory markers in reducing mortality—a retrospective cohort study based on NHANES 1999–2018 - Liu, Xin; Fan, Xuefei; Li, Chenggong; Liang, Xinquan; Hu, Pingping; Zhang, Jiandong (Translational Cancer Research; Vol 15, No 4 (April 30, 2026): Translational Cancer Research, 2026)
Although physical activity is recommended by major clinical guidelines to improve quality of life during cancer treatment, evidence regarding its association with survival—particularly cancer-specific and cardiovascular mortality—remains limited. Moreover, whether peripheral blood immune and inflammatory markers (PBIMs) might help explain this association has not been adequately explored in large, real-world cancer survivor populations. This study aimed to examine the associations between physical activity and all-cause, cancer-specific, and cardiovascular mortality in cancer survivors, and to explore the potential role of PBIMs in these associations.